1992
DOI: 10.1095/biolreprod46.5.853
|View full text |Cite
|
Sign up to set email alerts
|

Maturation, Fertilization, and Development of Dog Oocytes in Vitro1

Abstract: Preovulatory oocytes were collected from ovaries of beagle bitches that had received superovulatory treatment. They were cultured in a modified Krebs-Ringer bicarbonate solution containing 10% fetal calf serum and 30 mg/L gentamicin sulfate for up to 72 h. About 32% of oocytes reached metaphase II by 72 h of culture. When these in vitro-matured oocytes were inseminated with ejaculated beagle spermatozoa that had been preincubated for 4 h, sperm penetration of the zona pellucida started about 1 h after insemina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
47
1
4

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 0 publications
7
47
1
4
Order By: Relevance
“…In the present study, however, when the oocytes collected from ovaries at the follicular phase were cultured for 72 h, 45% of the oocytes achieved MII, including parthenogenetically activated oocytes (4%). This rate was higher than that reported by Yamada et al [9] in which 32% of the oocytes from superovulated bitches reached MII. In the present study, only oocytes with > 110 µm were used for maturation culture and they were cultured in medium supplemented with bitch serum.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…In the present study, however, when the oocytes collected from ovaries at the follicular phase were cultured for 72 h, 45% of the oocytes achieved MII, including parthenogenetically activated oocytes (4%). This rate was higher than that reported by Yamada et al [9] in which 32% of the oocytes from superovulated bitches reached MII. In the present study, only oocytes with > 110 µm were used for maturation culture and they were cultured in medium supplemented with bitch serum.…”
Section: Discussioncontrasting
confidence: 72%
“…In the IVM of canine oocytes, some studies have demonstrated that full meiotic maturation occurs after 24-48 h of in vitro culture [4,5], while other studies indicate that the oocytes cultured for 72-96 h achieved the highest maturation rates [6][7][8]. Yamada et al [9] suggested that oocytes from superovulated bitches achieve the highest maturation rates at 72 h of maturation culture, while oocytes from non-superovulated bitches show no tendency for increased maturation rates on culturing for up to 144 h. On the contrary, only four reported studies have shown the development of in vitro-matured and fertilized oocytes to the early embryo stage [9][10][11][12]. In the four studies, the oocytes were collected from bitches at various oestrous stages, matured for various incubation times (24-72 h) and fertilized with spermatozoa.…”
Section: Introductionmentioning
confidence: 99%
“…Culture media such as Tissue Culture Medium 199, modified Krebs Ringer Bicarbonate or Ham F-10 with or without serum or hormonal supplementation [4,27,28,44,45] have been used for IVM, but the requirements of canine oocytes in culture have not yet been elucidated. Recently, Hewitt and England [13] investigated the effect of using an environment different from that normally used in studies of mammalian oocyte maturation in vitro and more similar in composition to oviductal fluid.…”
Section: In Vitro Embryo Production In Dogsmentioning
confidence: 99%
“…In 1992, Yamada et al [44] reported 2% of inseminated oocytes that reached the 8-cell stage and recently Otoi et al [29] obtained one blastocyst out of 217 inseminated oocytes.…”
Section: In Vitro Fertilization and Embryo Developmentmentioning
confidence: 99%
“…Bitch oocytes are ovulated at the germinal vesicle stage and require 2 to 5 days for the completion of meiotic maturation [7,10,12]. However, the investigation of in vitro maturation of domestic bitch oocytes has been limited to a small number of studies [4,7,9,11], in contrast with other mammalian species. The present study was conducted to examine the number of oocytes recovered from individual bitches at various stages of the estrous cycle by the slicing method and the meiotic competence of recovered oocytes.…”
mentioning
confidence: 99%